Optimización de costos en la construcción del PAD, mediante el control y la gestión operativa por Stracon GyM en Minera Shahuindo” - Cárdenas Salazar, Silvia Maricela (2017)
The present work is orientated to the of the construction program's fulfillment and costs reduction of the lixiviation pad in Cía Minera Shahuindo. Where one has deficiencies in the unitary operations that conform the of the construction process, destined to execute them with efficiency, taking care of her his costs's significancia; They have done than continuously go away (subj) designing destined modes to better achievements. Our principal objective is to comply with of the construction program and to reduce costs, by means of the operating steps's application and control during the execution of Lixiviación's pad, herein occasion the stage 2A, the analysis procedure of data was based on the procedure in order to the hours operated control of teams and machinery weighed and; And in order to the application and the methodology's fulfillment, we have elements that conform it I have a meal : Procedures, documents and performances analysis. The knowing efficiency, operating steps and control in the different processes of pads's construction is going to be very useful and indispensable to us in the engineering projects, in them that ground levelings be sold off(subj). The unitary operations that conform the of the construction process of the lixiviation PAD, they play a role very important in solidum the of the construction cycle, in order to it the personnel must be trained and once was capacitated in the execution of the works, the advances that one obtain in and his performance's importance. following work understands : The definition, the problem formulation justification, I confer an objective aspect to of the investigation, place in where develops him the investigation, the machinery's description utilized, aftermaths, conclusions and recommendations methodology of the investigation, analysis of the performance of the machinery, discussion.